2008
DOI: 10.1007/s10519-007-9188-6
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Assignment of Quantitative Trait Loci Influencing Modified Hole Board Behavior in Laboratory Mice using Consomic Strains, with Special Reference to Anxiety-related Behavior and Mouse Chromosome 19

Abstract: Male mice from a panel of chromosome substitution strains (CSS, also called consomic strains or lines)-in which a single full-length chromosome from the A/J inbred strain has been transferred onto the genetic background of the C57BL/6J inbred strain-and the parental strains were examined in the modified hole board test. This behavioral test allows to assess for a variety of different motivational systems in parallel (i.e. anxiety, risk assessment, exploration, memory, locomotion, and arousal). Such an approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 39 publications
6
41
0
Order By: Relevance
“…Thus a high anxiety characteristic might not necessarily be detrimental to an animal's state of welfare as long as an individual is able to adapt, resulting in a decrease in anxiety towards a specific challenge over time [4], [6], [8]. Given that the process of selection and inbreeding in laboratory mice has resulted in the (unintentional) co-selection of emotional traits (see for example [8], [11], [13], [14], [44], [45]), we hypothesize that standard housing and treatment protocols for mice as a species may be insufficient to safeguard the welfare of different mouse (sub)strains equally. Compared to other strains, different 129 substrains reveal a reduced ability to adapt to exposure to novelty.…”
Section: Discussionmentioning
confidence: 99%
“…Thus a high anxiety characteristic might not necessarily be detrimental to an animal's state of welfare as long as an individual is able to adapt, resulting in a decrease in anxiety towards a specific challenge over time [4], [6], [8]. Given that the process of selection and inbreeding in laboratory mice has resulted in the (unintentional) co-selection of emotional traits (see for example [8], [11], [13], [14], [44], [45]), we hypothesize that standard housing and treatment protocols for mice as a species may be insufficient to safeguard the welfare of different mouse (sub)strains equally. Compared to other strains, different 129 substrains reveal a reduced ability to adapt to exposure to novelty.…”
Section: Discussionmentioning
confidence: 99%
“…The QTL on chromosome 4 has been identified previously as relevant to activity. This chromosome has been identified in a number of open‐field activity studies (Gill & Boyle 2005; Henderson et al 2004; Laarakker et al 2008; Singer et al 2005; Turri et al 2001a,b). Although the experimental differences between arenas used in this and the other studies might determine the presence or absence of some QTL, finding a common QTL across multiple studies suggests a particularly robust genetic pleiotropy at this locus.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognized that a multifactorial etiology underlies rodent behavior in short‐term ethological tests (Archer 1973; Blizard et al 2007; Stanford 2007; Takahashi et al 2006). Consistent with such complexity, quantitative trait locus (QTL) studies with mice have identified a polygenic system using a variety of test instruments (Caldarone et al 1997; Flint et al 1995; Gill & Boyle 2005; Henderson et al 2004; Laarakker et al 2008; Singer et al 2005; Turri et al 2001a,b), and attempts have been made to associate individual QTL with specific biobehavioral processes (Turri et al 2001a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Laarakker et al's study [26] reporting a contribution of the Y NPAR to anxiety-related behavior in mice, strengthens the hypothesis of an effect of the Y NPAR or brain BE, given that BE is considered as a stress hormone [27][29].…”
Section: Introductionmentioning
confidence: 75%